Kendala Bagi Pekerja Pariwisata Di Seminyak, Bali Dalam Penggunaan Bahasa Inggris - Suadnyana, I Wayan; Koeswiryono, Dika Pranadwipa (Jurnal Ilmiah Pariwisata; Vol 27 No 3 (2022): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v27i3.1633, 2022)
The language used internationally for communication is English. Therefore mastery of English is mandatory for all workers in the tourism sector. Tourism workers who communicate effectively in English provide an efficient service. Meanwhile, those who speak inadequate English tend to provide less efficient services due to communication barriers between foreign tourists and tourism workers. Based on these facts, the researcher will examine tourism workers' obstacles, especially in ​​Seminyak, Bali, in using tourism English. The method used in this study is a quantitative descriptive method. Data were obtained through questionnaires and interviews with respondents consisting of 54 tourism workers who work in tourism workplaces located in Seminyak, Bali province. The results showed that most of the tourism workers experienced speaking as their biggest obstacle (44.4%, followed by listening (29.6%), reading (14.8%), and writing (11.1%). This research can be suggested to focus on improving the skills of tourism workers in English, especially speaking skills, should be a priority, and formulate the best method to improve speaking skills for future tourism workers, especially in Bali. Keywords : Seminyak, Tourism Worker, English, Obstacles